Panel Discussion 1 | Investing in open infrastructure and service: The benefits and challenges at University of Hong Kong - XIAO, Jesse (Institutional Knowledge at Singapore Management University, 2021)
Covered the open infrastructure used by University of Hong Kong for Scholar Hub on DSpace, DataHub, DMP Platform on DMPTools, Ejournal service on OJS, Research Intelligence Hub (on-going), new research output system (on-going). Some of the challenges encountered when using open infrastructure.